DEVELOPMENT OF TEACHING MATERIALS READING COMPREHENSION BASED ON COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) STRATEGY AS CHARACTER EDUCATION IN CLASS VI ELEMENTARY SCHOOL - Nofrico Afendi; Mudjiran Mudjiran; Darnis Arif; Misliati Misliati (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
This study aims to develop learning to read understanding based on CIRC strategies as an effort to instill character education in grade VI elementary schools that is valid, practical, and effective. This type of research is research and development. The development model used is a 4-D model consisting of the stages of defining, designing, developing and disseminating. This research data from the validity test was obtained through the validation sheet of teaching materials. Practicality data was collected through observation sheets of the implementation of the lesson plans, teacher and student response questionnaires, and interviews with teachers. Based on the validity test obtained the percentage of RPP 91.3% with a very valid category. This means that the RPP component is in accordance with the Ministry of Education Regulation No. 41 of 2007. The results of the validity of teaching materials with a percentage of 90% with a very valid category, this means that teaching materials that have been developed are in accordance with curriculum demands. The practicality test results of the implementation of lesson plans with a percentage of 95.3% with the category of very practical, during the trial teacher has no difficulty in implementing learning. The percentage of teacher responses to the questionnaire was 92.5% with a very practical category, the teacher stated the teaching material developed was different from the previous teaching material, easy to use in learning. The percentage of questionnaire responses of students was 90.2% with a very practical category, teaching materials were also interesting for students because they were designed with more interesting colors and drawings. Judging from the effectiveness test, the character values in the trials averaged 82.8%, while in the distribution of the students' character values 81%. In reading skills, the percentage while testing is 85%, while in the spread is 89%. Based on the above description, it can be concluded that the reading materials for understanding CIRC-based strategies developed can be declared valid, practical and effective